Using science and psychology to improve the dissemination and evaluation of scientific work - Buttliere, Brett T. (Frontiers in Computational Neuroscience, 2014)
Here I outline some of what science can tell us about the problems in psychological publishing and how to best address those problems. First, the motivation behind questionable research practices is examined (the desire to get ahead or, at least, not fall behind). Next, behavior modification strategies are discussed, pointing out that reward works better than punishment. Humans are utility seekers and the implementation of current change initiatives is hindered by high initial buy-in costs and insufficient expected utility. Open science tools interested in improving science should team up, to increase utility while lowering the cost and risk associated with engagement. The best way to realign individual and group motives will probably be to create one, centralized, easy to use, platform, with a profile, a feed of targeted science stories based upon previous system interaction, a sophisticated (public) discussion section, and impact metrics which use the associated data. These measures encourage high quality review and other prosocial activities while inhibiting self-serving behavior. Some advantages of centrally digitizing communications are outlined, including ways the data could be used to improve the peer review process. Most generally, it seems that decisions about change design and implementation should be theory and data driven.